Lecturers’ Reasoning in Using Digital Technology: A Cognitive Approach in Learning Process - Harisa Mardiana (CV. Media Digital Publikasi Indonesia, 2023)
This research aims to investigate the reasoning of lecturers in using digital technology and its impact on cognitive approaches. Moreover, we find out the lecturer's use of digital technology in the learning process and determine the reasoning relationship between the use of digital technology and cognition. Problems occurred during the COVID-19 pandemic, where many lecturers needed to be stronger in digital mastering technology and low in its use. Some lecturers think that WhatsApp is online learning, where online learning requires interaction and not just sending news or subjects. Furthermore, many students feel pressured to be taught by lecturers like this, so several classes are closed because there are no students. This study used a mixed-method approach with 109 respondents. Data collection uses a questionnaire distributed through Google Forms, and the qualitative data uses interviews with eight respondents. The results show that 50.5% of respondents can use digital technology, and 49.5% must learn, practice, and receive digital technology training. Furthermore, this research implies that lecturers with critical thinking can quickly master digital technology and simultaneously teach fellow lecturers to use digital technology